Features of the first-year students’ adaptation for studying at a technical university - Komarova, K. (ТДАТУ, 2018)
EN: The article analyzes the features of the first-year students' adaptation at a technical university. It deals with the psychological and pedagogical features of the adaptation process of first-year students, reveals qualitative differences as well as the significance of the problem, and presents the results of psycho-pedagogical research. У статті аналізуються особливості адаптації студентів першого курсу технічного університету. UK: Розглядаються психологічні та педагогічні особливості процесу адаптації студентів першого курсу. Виявляються якісні відмінності та значимість проблеми, а також представлені результати психолого-педагогічного дослідження.
Keywords: adaptation process; students’ adaptation; аdaptation